2019
DOI: 10.1111/1471-0528.15855
|View full text |Cite
|
Sign up to set email alerts
|

Placental growth factor testing for suspected pre‐eclampsia: a cost‐effectiveness analysis

Abstract: Objective To calculate the cost‐effectiveness of implementing PlGF testing alongside a clinical management algorithm in maternity services in the UK, compared with current standard care. Design Cost‐effectiveness analysis. Setting Eleven maternity units participating in the PARROT stepped‐wedge cluster‐randomised controlled trial. Population Women presenting with suspected pre‐eclampsia between 20+0 and 36+6 weeks’ gestation. Methods Monte Carlo simulation utilising resource use data and maternal adverse outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…Although this cohort included 287 women, of which 19 (7%) had CKD, median and interquartile ranges for serum creatinine were 0.58 mg/dl and 0.50-0.70 mg/dl, respectively. More recently, a randomized controlled trial of revealed versus concealed PlGF testing was shown to reduce the time to diagnosis and maternal adverse event rate, with no difference in perinatal outcomes (19), at a cost saving of £149 ($190) per patient compared with usual surveillance, including the test cost of £70 ($90) (21). Only 4% of women in this trial had CKD.…”
Section: Preeclampsia and Angiogenesismentioning
confidence: 75%
“…Although this cohort included 287 women, of which 19 (7%) had CKD, median and interquartile ranges for serum creatinine were 0.58 mg/dl and 0.50-0.70 mg/dl, respectively. More recently, a randomized controlled trial of revealed versus concealed PlGF testing was shown to reduce the time to diagnosis and maternal adverse event rate, with no difference in perinatal outcomes (19), at a cost saving of £149 ($190) per patient compared with usual surveillance, including the test cost of £70 ($90) (21). Only 4% of women in this trial had CKD.…”
Section: Preeclampsia and Angiogenesismentioning
confidence: 75%
“…Our cost effectiveness analysis has been previously reported. The resource use data showed that PlGF was overall cost saving, with an increase in antenatal inpatient costs for those with abnormal PlGF alongside a reduction in outpatient attendances in those with a normal result, suggesting improved risk stratification with PlGF testing [24] . As we did not undertake a more detailed process evaluation, the exact components of changes in the antenatal care pathways that contributed to the reduction in severe maternal adverse outcomes may remain unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Initial studies using economic modelling demonstrated that PlGF‐based testing may afford a cost saving of between UK£330 and UK£1,032 per woman tested 17,18 . In a more recent study describing their cost‐effectiveness analysis of the PARROT trial, Duhig and colleagues found a total cost saving of UK£149 per woman, based on UK£70 per Triage PlGF test 19 . Given that there were 646 794 births in England in 2017 and 10% of pregnant women have suspected pre‐eclampsia, with 30% of these presenting prior to 37 weeks' gestation, PlGF testing could be performed in approximately 38 800 women per year.…”
Section: Evidence For the Triage Plgf Testmentioning
confidence: 99%
“…The cost‐saving seen in this budget impact analysis is more conservative than previous hypothetical savings. The authors conclude that this may be due to improved clinical risk stratification, leading to appropriate redistribution of resources, rather than an overall reduction of resource use 19 …”
Section: Evidence For the Triage Plgf Testmentioning
confidence: 99%